Addition of a volcanic rockdust to soils has no observable effects on plant yield and nutrient status or on soil microbial activity - Ramezanian, Atefeh; Dahlin, A. Sigrun; Campbell, Colin D.; Hillier, Stephen; Mannerstedt-Fogelfors, Birgitta; Öborn, Ingrid (Plant and soil, 2013)
Background and Aims Rising costs and pressure on supplies of commercial mineral fertilizers and increasing markets for organically produced foods and feeds have led to a growing interest in soil amendments to supply plant nutrients. Rockdust is a byproduct of quarrying and its effectiveness to supply plants with nutrients has been a contested issue and there have been no assessments of its effect on soil biota other than plants. The aim of this study was to assess the effect of a commercially-available volcanic rockdust application on crop growth and element concentrations for a wide range of macro and microelements and the response of soil microbial communities to rockdust due to the potential alteration in soil mineralogy. Methods A three-year controlled outdoor-growing experiment was conducted on three different soil types with two wheat cultivars in the first year following rockdust application and with forage species in the third year. Results Our results show that the tested rockdust had no positive or negative effect on plant growth or nutrient composition. In addition, the microbial response to added substrates, a sensitive measure of changes in soil environment, were unaltered by the rockdust. Conclusions As the rockdust had no nutrient or toxic effect it can probably be considered as an inert material which at least causes no harm but equally has no demonstrable ecological or agricultural benefit.